Interleukin-6 Elevation Is a Key Pathogenic Factor Underlying COVID-19-Associated Heart Rate-Corrected QT Interval Prolongation - Lazzerini, Pietro Enea; Accioli, Riccardo; Acampa, Maurizio; Zhang, Wen-Hui; Verrengia, Decoroso; Cartocci, Alessandra; Bacarelli, Maria Romana; Xin, Xiaofeng; Salvini, Viola; Chen, Ke-Su; Salvadori, Fabio; D’errico, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Heart rate-corrected QT interval (QTc) prolongation is prevalent in patients with severe coronavirus disease 2019 (COVID-19) and is associated with poor outcomes. Recent evidence suggests that the exaggerated host immune-inflammatory response characterizing the disease, specifically interleukin-6 (IL-6) increase, may have an important role, possibly via direct effects on cardiac electrophysiology. The aim of this study was to dissect the short-term discrete impact of IL-6 elevation on QTc in patients with severe COVID-19 infection and explore the underlying mechanisms. Methods We investigated the following mechanisms: (1) the QTc duration in patients with COVID-19 during the active phase and recovery, and its association with C-reactive protein (CRP) and IL-6 levels; (2) the acute impact of IL-6 administration on QTc in an in vivo guinea pig model; and (3) the electrophysiological effects of IL-6 on ventricular myocytes in vitro. Results In patients with active severe COVID-19 and elevated IL-6 levels, regardless of acute myocardial injury/strain and concomitant QT-prolonging risk factors, QTc was significantly prolonged and rapidly normalized in correlation with IL-6 decrease. The direct administration of IL-6 in an in vivo guinea pig model acutely prolongs QTc duration. Moreover, ventricular myocytes incubated in vitro with IL-6 show evident prolongation in the action potential, along with significant inhibition in the rapid delayed rectifier potassium current (IKr). Conclusion For the first time, we demonstrated that in severe COVID-19, systemic inflammatory activation can per se promote QTc prolongation via IL-6 elevation, leading to ventricular electric remodeling. Despite being transitory, such modifications may significantly contribute to arrhythmic events and associated poor outcomes in COVID-19. These findings provide a further rationale for current anti-inflammatory treatments for COVID-19, including IL-6-targeted therapies.